A Case Study Of Strategies And Management Of Carrefour Europe - Hee, Kong Ban (2004)
This study has been divided in two parts. The first part would be the case writing includes Carrefour background, histories, stores, management and strategies. The second part would start having detail analysis including both internal and external analysis using tools like PEST and SWOT based on information in Part 1.